Simulasi Sudut Serang Aliran Air Terhadap Kincir Air Aliran Bawah - Sauf, Muhamad; Balaka, Ridway; Hasanudin, La (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2019)
Waterwheels become one of the solutions to increase the need for power supplies especially in areas that are not able to reach electrical networks that have sufficient water resources. The research aims to determine the influence of change into the dyeing of the blade and slope of the blade angle to the power and efficiency of the lower flow waterwheel. The manufactured waterwheel model is an undershot type of 16-piece blade. The outer diameter of the Ferris wheel is 0.2 m and the diameter is 0.12 m. Blade is flat in size (0, 04x0,04) m. The Ferris wheel is made up of as many as 3 pieces with a tilt difference of the blade angle of 00 from the shaft, 100 of the shaft, and 200 of the shaft. The results showed that on immersion blade 0.01 m obtained power 0.16 Watt and efficiency 12.24%, in blade dyeing 0.02 m obtained power 0.162 Watt and efficiency 12.42 %, and dyeing 0.03 m obtained power 0.176 Watt and efficiency 13.45 %. While at the slope of a blade angle is obtained by 0.16 Watt power and efficiency 12.24 %, on the slope of blade angle of 100 acquired power 0.302 Watt and efficiency 23.1 %, and at the slope of a blade angle, 200 acquired power 0.447 Watt and efficiency 34.18 %. So it can be said that the more in the immersion blade the greater the power and efficiency of the Ferris wheel, and the more oblique blade angle than the greater the power and efficiency of the windmill.Keywords: Waterwheel, blade, angle, power, and efficiency